Fast and Simple Preparation of Iron‐Based Thin Films as Highly Efficient Water‐Oxidation Catalysts in Neutral Aqueous Solution1. (27th February 2015) - Wu, Yizhen; Chen, Mingxing; Han, Yongzhen; Luo, Hongxia; Su, Xiaojun; Zhang, Ming‐Tian; Lin, Xiaohuan; Sun, Junliang; Wang, Lei; Deng, Liang; Zhang, Wei; Cao, Rui
Abstract Water oxidation is the key step in natural and artificial photosynthesis for solar‐energy conversion. As this process is thermodynamically unfavorable and is challenging from a kinetic point of view, the development of highly efficient catalysts with low energy cost is a subject of fundamental significance. Herein, we report on iron‐based films as highly efficient water‐oxidation catalysts. The films can be quickly deposited onto electrodes from FeII ions in acetate buffer at pH 7.0 by simple cyclic voltammetry. The extremely low iron loading on the electrodes is critical for improved atom efficiency for catalysis. Our results showed that this film could catalyze water oxidation in neutral phosphate solution with a turnover frequency (TOF) of 756 h−1 at an applied overpotential of 530 mV. The significance of this approach includes the use of earth‐abundant iron, the fast and simple method for catalyst preparation, the low catalyst loading, and the large TOF for O2 evolution in neutral aqueous media.